Efektifitas Kinerja Pemerintah Desa Sukorambi dalam Pelayanan Pembuatan Kartu Keluarga di Kabupaten Jember - Oktavianti, Tania Dwi; Wicaksono, Itok (Indonesian Journal Publisher, 2023)
This research aims to analyze the effectiveness of the Sukorambi Village Government's performance in providing Family Card services in Jember Regency. This research uses a qualitative approach with a case study method. The object of the research is the service process for making Family Cards at the Sukorambi Village Government. Data was collected through observation, interviews with service personnel, and documentation studies. Data analysis was carried out using data reduction, data display and data verification techniques. The results of the research show that the Sukorambi Village Government has made various efforts to increase the effectiveness of the Family Card making service. Some of the steps taken include improving service quality, training for service personnel, and implementing information technology. However, there are several obstacles faced by the Village Government in improving the effectiveness of the performance of Family Card making services, such as limited human resources and limited technology. This research concludes that although there have been efforts made by the Sukorambi Village Government, further steps are still needed to improve the effectiveness of the performance of Family Card making services in order to provide more efficient and quality services to the community.